Hybrid foldamer with unique architecture from conformationally constrained aliphatic-aromatic amino acid conjugate - Srinivas, Deekonda; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Tetrahedron, 2006)
In this paper, we describe the design and synthesis of a novel hybrid foldamer, derived from a conformationally constrained aliphatic-aromatic amino acid conjugate that adopts a well-defined, compact, three-dimensional structure, governed by a combined conformational restriction imposed by the individual amino acids from which the foldamer is composed. Conformational investigations confirmed the prevalence of a unique doubly bent conformation for the foldamer, in both solid and solution states, as evidenced from single crystal X-ray and 2D NOESY studies, respectively. The findings suggest that constrained aliphatic-aromatic amino acid conjugates offer new avenues for the de novo design of hybrid foldamers with distinctive structural architectures. Furthermore, the de novo design strategy disclosed herein has the potential for significantly augmenting the `tool-box' of the modern day peptidominetic chemist, as well as providing a novel approach to the field of rational design. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; Conformation; Foldamer; Peptidomimetics

Helical folding in heterogeneous foldamers without inter-residual backbone hydrogen-bonding - Priya, Gowri; Kotmale, Amol S.; Gawade, Rupesh L.; Mishra, Deepti; Pal, Sourav; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
This communication describes a set of hybrid foldamers that do not feature inter-residual, but intra-residual backbone hydrogen-bonding, yet adopt a preferentially folded conformation displaying right-handed helical architecture. Conformational ordering is apparently due to the combined conformational restrictions imposed by the conformationally restricted individual amino acid residues with which the oligomers are made of.

Heterogeneous foldamers from aliphatic-aromatic amino acid building blocks: current trends and future prospects - Nair, Roshna V.; Vijayadas, Kuruppanthara N.; Roy, Arup; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2014)
Chemists' constant pursuit of understanding of the underlying principles of nature's most intricate phenomenon such as protein folding has led to the development of the field of foldamers. The emergence of diverse classes of unnatural amino acid building blocks has unleashed countless opportunities to design, develop and explore the structural and functional aspects of synthetic peptides. One current trend in foldamer chemistry is the heterofoldamer approach, which involves systematic stoichiometric variation of various natural/unnatural amino acid residues, leading to conformational ordering with intriguing structural architectures. In this regard, the incorporation of aromatic amino acids provides efficient structural rigidification and tunability to the molecular scaffolds, which can exhibit a range of secondary structural features. Recent times have witnessed an upsurge of foldamers featuring aliphatic-aromatic residues with diverse structural propensities. This review is an effort to cover this rapidly developing field of foldamer science and also to envisage its future perspectives.
Keywords: Amino acids; Conformation analysis; Foldamers; hydrogen bonding; Peptides; Stacking interactions

Helically structured peptide architecture engineered using dimedone as a rigid organic scaffold - Nadimpally, Krishna C.; Madica, Krishnaprasad; Kotmale, Amol S.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
This communication reports the use of a rigid organic scaffold to attach two unsymmetrical peptide chains on a single carbon atom. The approach describes the step-by-step attachment of peptide chains to the rigid dimedone template (5,5-dimethyl-1,3-cyclohexanedione) - a molecular scaffold that directs orientation of the peptide helices in a well-defined arrangement via intra-molecular hydrogen bonding. The overall topology of the final molecules was studied using CD spectroscopy which suggested existence of helical architecture.

Histidinal-based potent antimalarial agents - Meena, Chhuttan L.; Hingamire, Tejashri; Gupta, Tanya; Deshmukh, Bhagyashree; Karmodiya, Krishanpal; Joshi, Rakesh; Shanmugam, Dhanasekaran; Sanjayan, Gangadhar J. (ChemMedChem, 2023)
Herein we report the synthesis and evaluation of peptide-histidinal conjugated drug scaffolds, which have the potential to target the hemoglobin-degrading proteases falcipain-2/3 from the human malaria parasite. Scaffolds with various substitutions were tested for antimalarial activity, and compounds 8 g, 8 h, and 15 exhibited EC50 values of similar to 0.018 mu M, similar to 0.069 mu M, and similar to 0.02 mu M, respectively. Structure-based docking studies on falcipain-2/3 proteases (PDB:2GHU and PDB:3BWK) revealed that compounds 8 g, 8 h, and 15 interact strongly with binding sites of falcipain-2/3 in a substrate-like manner. In silico ADME studies revealed that the molecules of interest showed no or minimal violations of drug-likeness parameters. Further, phenotypic assays revealed that compound 8 g and its biotinylated version inhibit hemoglobin degradation in the parasite food vacuole. The identification of falcipain-2/3 targeting potent inhibitors of the malaria parasite can serve as a starting point for the development of lead compounds as future antimalarial drug candidates.
Keywords: artemisinin; chloroquine; digestive vacuole; docking; falcipains; falciparum; P